Construction information frameworkthe role of classification systems - Hipólito Sousa (2016)
This paper focuses on understanding the role of Construction Information Classification Systems (CICS). Information Classification Systems (ICS) that range several economic activities including construction are also explored in order to find touch points and define future trends. This starts with an overview of classification systems, framed with ISO 12006-2: 2015. Two different realities, Norway and Portugal, were studied following ISO framework, providing a vision of the developments and applicability of both types of classification systems. Needs for further development have been discussed in a relation to the new possibilities of BIM. The outcome of this study is a list of proposals for further developments. Classification systems represent information. Information coherency is fundamental towards the objectives of efficiency on the industry. The use of BIM can enforce the development of a new generation of CICS. (c) 2016 Taylor & Francis Group.